CD4:CD8 Ratio and CD8 Cell Count and Their Prognostic Relevance for Coronary Heart Disease Events and Stroke in Antiretroviral Treated Individuals: The Swiss HIV Cohort Study - Chammartin, Frédérique (J Acquir Immune Defic Syndr, 2022)
HIV infection leads to a persistent expansion of terminally CD8 T cells and CD8 T suppressor cells, a marker of chronic immune activation leading to a low CD4:CD8 ratio that may persist in the presence of potent antiretroviral therapy and regained CD4 helper cells. It remains unclear whether a low CD4:CD8 ratio is associated with cardiovascular diseases. METHODS: We conducted an observational cohort study to investigate the association of immune depression and activation as characterized by the proxy of the CD4:CD8 ratio on the hazard of coronary heart disease (CHD) and stroke among treated individuals living with HIV, while accounting for viral load and known risk factors for cardiovascular diseases and exposure to abacavir or protease inhibitors. We used Cox proportional hazard models with time-dependent cumulative and lagged exposures to account for time-evolving risk factors and avoid reverse causality. RESULTS: CD4, CD8, and CD4:CD8 immunological markers were not associated with an increased hazard for CHD. CD8 cell count lagged at 12 months above 1000 cells per μL increased the hazard of stroke, after adjusting for sociodemographics, cardiovascular risk factors, and exposure to specific types of antiretroviral drugs. CONCLUSIONS: This analysis of treated HIV-positive individuals within a large cohort with long-term follow-up does not provide evidence for a prognostic role of immune dysregulation regarding CHD. However, increased CD8 cell count may be a moderate risk factor for stroke. Early detection and treatment of HIV-positive individuals are crucial for an optimal immune restoration and a limited CD8 cells expansion.